The incidence of first stroke in pregnant and non-pregnant women of childbearing age: a population-based cohort study from England - Ban, Lu; Sprigg, Nikola; Nelson-Piercy, Catherine; Bath, Philip M.W.; Ludvigsson, Jonas F.; Stephansson, Olof; Tata, Laila J. (Wiley, 2017)
Background: Pregnant women may have an increased risk of stroke compared to non-pregnant women of similar age, but the magnitude and the timing of such risk are unclear. We examined the risk of first stroke event in women of childbearing age and compared the risk during pregnancy and in the early postpartum period to background risk outside these periods. Methods and Results: We conducted an open cohort study of 2,046,048 women aged 15-49 years between 1st April 1997 and 31th March 2014 using linked primary (Clinical Practice Research Datalink) and secondary (Hospital Episode Statistics) care records in England. Risk of first stroke was assessed by calculating the incidence rate of stroke in antepartum, peripartum (2 days before until 1 day after delivery), early (first six weeks) and late (second six weeks) postpartum periods, compared with non-pregnant time using a Poisson regression model with adjustment for maternal age, socioeconomic group and calendar time. A total of 2,511 women had a first stroke. The incidence rate of stroke was 25.0 per 100,000 person-years (95% confidence interval 24.0-26.0) in non-pregnant time. The rate was lower antepartum (10.7/100,000 person-years, 7.6-15.1), but 9-fold higher peripartum (161.1/100,000 person-years, 80.6-322.1) and 3-fold higher early postpartum (47.1/100,000 person-years, 31.3-70.9). Rates of ischaemic and haemorrhagic stroke both increased peripartum and early postpartum. Conclusions: Although the absolute risk of first stroke is low in women of childbearing age, health care professionals should be aware of a considerable increase in relative risk during the peripartum and early postpartum periods.